Characterisation of two unusual cases of haemoglobin Bart’s hydrops foetalis caused by – and large novel α-globin gene cluster deletions - Yunan Wang; Ying Xiong; Chang Liu; Jian Lu; Jicheng Wang; DanQing Qin; Ling Liu; Jing Wu; Xin Zhao; Liyuan Fang; Li Du; Aihua Yin (Journal of international medical research, 2021)
Background We describe 2 unusual haemoglobin (Hb) Bart’s hydrops cases that could not be explained by traditional factors. Case presentation: Two families with a diagnosis or history of foetal hydrops were enrolled. A suspension-array system was used to detect the 23 most frequent mutations in southern China. Multiplex ligation-dependent probe amplification (MLPA) was used to screen for possible deletions. Precise characterisation of the breakpoints of the novel variants and uniparental disomy analysis were performed using a single nucleotide polymorphism (SNP) array. Quantitative fluorescence PCR was used to eliminate maternal cell contamination and nonpaternity. In case 1, the suspension-array system indicated a maternal heterozygous (– SEA /) deletion, and the paternal sample was negative. The foetal hydrops was caused by the maternal (– SEA /) deletion and a de novo α-globin gene deletion (– 193 ). In case 2, the paternal sample had a heterozygous (– SEA /) deletion, and MLPA and SNP array analysis revealed a large maternal deletion (– 227 ) that encompassed the α-globin gene, which explained the history of Hb Bart’s foetal hydrops. Conclusions Our cases describe 2 new α 0 -thalassaemia deletions and illustrate the importance of using a combination of methods to detect rare types of α-thalassaemia.